Analisis Isi Kekerasan Verbal terhadap Agama Islam dalam Konten Youtube Jozeph Paul Zhang - Kurniawan, Ilham; Sikumbang, Ahmad Tamrin; Muktarruddin, Muktarruddin (ANWARUL, 2023)
In general to find out verbal abuse in Jozeph Paul Zhang's youtube content. And specifically to find out about verbal violence against the Islamic religion in Jozeph Paul Zhang's Youtube Content. The research method uses a qualitative approach to content analysis with the research subject, namely Jozeph Paul Zhang's YouTube content, data collection techniques using coding sheets. Data analysis techniques use content analysis using the Roland Barthers method. The results of the research are: 1. The contents of Jozeph Paul Zhang's youtube content are hate speech (Head Speech). 2. As for verbal violence in Joseph Paul Zhang's youtube content, it can be found in videos that aired in April 2021 and February 2023 with verbal abuse sayings including: "Speaking of a prophetic voice because there are many injustices against minorities", "He said God is thirsty blood killed one thousand two hundred people", "Islamic Allah punishes his own people", "Muslims are repeatedly punished by Allah SWT, he says it's a trial" and "Muslims who are bastards and cant believe in gebleg teachings". The aims of this study are: 1. To find out the contents of Jozeph Paul Zhang's YouTube content. 2. To find out verbal violence against Islam in Jozeph Paul Zhang's YouTube content.